Floristic composition of cyanobacteria in a neotropical, eutrophic reservoir - Palacio, Hilda Maria (2015)
In order to know the flora of planktonic cyanobacteria, 24 water samples (May 2010–October 2013) from the Riogrande II Reservoir, Colombia (75o32′30′W–75o26′10′W and 6o33′50′N–6o28′07′N) were studied. The reservoir provides water to 1.4 million inhabitants in Medellin, Colombia (40 % of the total population). Among the cyanobacteria, we identified 11 morphospecies belonging to three families of the order Chroococcales (Merismopediaceae (2 species), Microcystaceae (3) and Synechococcaceae (1)), one of Oscillatoriales (Pseudanabaenaceae, 1 species) and one of Nostocales (Nostocaceae, 4 species). The genera with the highest number of taxa were Microcystis Kutzing ex Lemmermann and Dolichospermum (Ralfs ex Bornet et Flahault) Wacklin, Hoffmann & Komarek, both known to form dense blooms, many of them toxic. That is why the aim of this research is to understand the cyanobacterial species richness in the reservoir.